Arterial Structure and Function in Ambulatory Adolescents with Cerebral Palsy Are Not Different from Healthy Controls - Audra A. Martin; Lisa M. Cotie; Brian W. Timmons; Jan Willem Gorter; Maureen J. MacDonald (International Journal of Pediatrics)
Physical inactivity in youth with cerebral palsy (CP) places them at increased risk of developing cardiovascular disease. The current study assessed indices of arterial health in adolescents with CP, classified as levels I-II of the Gross Motor Function Classification System (GMFCS) (n=11, age 13.2±2.1 yr), in comparison to age- and sex-matched controls (n=11, age 12.4±2.3 yr). Groups were similar in anthropometric measurements, resting blood pressures, and heart rates. There were no group differences in brachial flow-mediated dilation (11.1±7.8 versus 6.1±3.6), carotid intima-media thickness (0.42±0.04 versus 0.41±0.03 mm), and distensibility (0.008±0.002 versus 0.008±0.002 mmHg) or central (4.3±0.6 versus 4.1±0.9 m/s) and peripheral pulse wave velocity (7.1±1.7 versus 7.6±1.1 m/s); CP versus healthy controls, respectively. Vigorous intensity physical activity (PA) was lower in the CP group (CP: 38±80 min versus controls: 196±174 min); groups were similar in light and moderate intensity PA levels. Arterial health of ambulatory youth with CP is not different from a control group despite lower vigorous PA levels. Similar studies need to examine individuals with more pronounced mobility limitations (GMFCS level III–V).